Antigua vision : Caribbean reality : perspectives of Prime Minister Lester Bryant Bird - Sanders, Sir Ronald (Hansib Pub. LondonGB, 2002)
Looks at issues that confroned the region over the period 1976-2001. Covers a range of topics, each of them crucial to the Caribbean's economic, social and political development.